2010
DOI: 10.1038/hr.2010.120
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of high-dose valsartan monotherapy in hypertension treatment: the ValTop study

Abstract: Early combination therapy is increasingly recommended in hypertension management because of increased risk of adverse effects with high-dose monotherapy. However, this risk is not necessarily increased for high doses of angiotensin receptor blockers (ARB). ValTop study compared efficacy and safety of high vs. conventional dose of valsartan in hypertensive patients. ValTop was a controlled, randomized, double-blind trial. Of 6035 screened subjects, 4004 mild-to-moderate hypertensive patients (mean seated diasto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 29 publications
2
7
0
4
Order By: Relevance
“…The results of the present study demonstrated the antihypertensive efficacy of once-daily 160 mg valsartan in Chinese patients with mild to moderate hypertension. The blood pressure reductions observed in the current study (15.6/11.1 mmHg for office SBP/DBP following 10 weeks treatment) were comparable to those obtained in previous studies (7,11,(19)(20)(21)(22)(23), which examined single-drug or combination valsartan therapy in patients with mild to moderate hypertension over a similar time frame. In the latter studies, mean SBP reductions between 10.2 and 16.5 mmHg were observed, whereas mean DBP reductions were between 5.3 and 10.3 mmHg.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The results of the present study demonstrated the antihypertensive efficacy of once-daily 160 mg valsartan in Chinese patients with mild to moderate hypertension. The blood pressure reductions observed in the current study (15.6/11.1 mmHg for office SBP/DBP following 10 weeks treatment) were comparable to those obtained in previous studies (7,11,(19)(20)(21)(22)(23), which examined single-drug or combination valsartan therapy in patients with mild to moderate hypertension over a similar time frame. In the latter studies, mean SBP reductions between 10.2 and 16.5 mmHg were observed, whereas mean DBP reductions were between 5.3 and 10.3 mmHg.…”
Section: Discussionsupporting
confidence: 76%
“…Antihypertensive efficacy of valsartan has been established over a range of doses, up to 320 mg/day, in North American and European hypertensive patient populations (7,8,18). The results of the present study demonstrated the antihypertensive efficacy of once-daily 160 mg valsartan in Chinese patients with mild to moderate hypertension.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…This allowed the identification of statistically significant differences between the effects of valsartan 160 and 320 mg. These observations clearly show that eBPM can safely and effectively be used in clinical research as an alternative to AuscBPM [17].…”
Section: Discussionmentioning
confidence: 60%
“…This notion is strengthened by the results of the ValTop study published in the present issue of Hypertension Research. 11 The ValTop study was a controlled, randomized, double-blind trial. A total of 4004 patients with uncomplicated mild-tomoderate hypertension (mean diastolic BP: 95-109 mm Hg) were started on a 4-week open-label treatment with valsartan 160 mg.…”
mentioning
confidence: 99%